PSIQUIATRÍA: UNA NECESIDAD PARA EL SISTEMA DE SALUD DEL PERÚ Y DEL MUNDO - Cedillo-Ramírez, Lucy (2018)
Abstract The World Health Organization defined mental health as a state of well-being in which the individual is aware of his own abilities, and is able to make a valuable contribution to his community1. On the contrary, the prevalence of mental disorders in the world is worrisome, to cite some figures, depression is a frequent mental disorder and one of the main causes of disability that affects more than 300 million people around the world; bipolar disorder affects around 60 million people worldwide; Approximately 21 million people suffer from schizophrenia; and about 47.5 million show clinical signs of dementia. It is expected that the prevalence of these diseases will increase due to the scarcity of psychiatry.In Peru, the situation in the area of mental health is similar; every year 20% of the adult population suffers from some type of mental disorder; and only 1 in 10 people who require treatment have access to health services. To guarantee the mental health care of more Peruvians, the Health Reform has incorporated specialized care in the Primary Healthcare Level. However, there are currently approximately 700 Peruvian psychiatrists, an amount with which it is impossible to cover care in the more than 7,000 health facilities in the country.In view of this global problem, it is urgent to find out about the factors that contribute to more medical students consider the choice of psychiatry as a medical specialty. Different studies worldwide and nationally suggest that the selection of the medical specialty is influenced mainly by personality and this is not alien to the choice of psychiatry as a specialty to study. In addition, among medical students there are significant differences in their vocational preferences according to sex; According to this, women are the ones who mostly choose psychiatry⁷. On the other hand, the experience in the course during the academic years of the medical career, provide a more realistic view of psychiatry, which contributes to more medical students are interested in pursuing the specialty later. DOI: https://doi.org/10.25176/RFMH.v18.n1.1275